Prevalence of Insulin Resistance in Adults Living with HIV: Implications of Alcohol Use - Simon, Liz (AIDS Res Hum Retroviruses, 2020)
Unhealthy alcohol use is prevalent among persons living with HIV (PLWH). Aging and increased survival of PLWH on antiretroviral therapy (ART) are complicated by metabolic dysregulation and increased risk of insulin resistance (IR) and diabetes mellitus. The objective of this study was to determine the prevalence and association of IR with unhealthy alcohol use in adult in-care PLWH. A cross-sectional analysis of metabolic parameters and alcohol use characteristics was conducted in adult PLWH enrolled in the New Orleans Alcohol Use in HIV (NOAH) Study. IR was estimated using homeostatic model assessment (HOMA-IR), triglyceride index, and McAuley index and beta cell function (HOMA-β). Alcohol use was assessed using Alcohol Use Disorders Identification Test (AUDIT)-C, 30-day timeline followback (TLFB), lifetime drinking history, and phosphatidylethanol (PEth) measures. A total of 351 participants, with a mean age [±standard deviation (SD)] of 48.1 ± 10.4 years, were included (69.6% male). Of these, 57% had an AUDIT-C score of 4 or greater, indicating unhealthy alcohol use. Mean body mass index (BMI) was 27.2 ± 7.0 kg/m(2), 36.4% met criteria for metabolic syndrome, and 14% were diagnosed with diabetes. After adjusting for education, race, BMI, smoking status, viral load, CD4 count, use of protease inhibitors, statins, or metformin; physical activity and diabetes diagnosis, HOMA-IR, and McAuley index were negatively associated with AUDIT-C, and HOMA-β cell function was negatively associated with AUDIT-C, PEth, and TLFB. Cross-sectional analysis of NOAH participants indicates that alcohol use is associated with decreased HOMA-β cell function, suggesting dysregulation of endocrine pancreatic function.